Treatment of Early Developed Peri-Implantitis in Fibula Graft Site - Zoran Tatić; Marija Bubalo; Nenad Petrović; Vitomir Konstantinović; Radomir Milović (University of Zagreb. School of Dental Medicine, 2021)
The fibula microvascular free flap technique and placement of dental endosseous implants seem to be viable options for reconstructing the mandible, following a resective jaw surgery. The causes of early failures of implants include bone overheating, latent infection by surgical trauma, the factors related with the implant, and overcompression. This case report reviews the mechanisms of early postimplantation bone loss, and suggests the course of treatment for early peri-implantitis for implants that show no mobility. Radiographs and clinical data presented have shown that the surgical treatment of early developed peri-implantitis using GBR methods in free fibula graft sites offers promising and stabile results.